41.8k views
0 votes
-5x -4y = -15 and -x + 4y = -3

User Wjchulme
by
5.2k points

1 Answer

3 votes

So the first thing you would want to do is rewrite the equation like so.

−x+4y=−3;−5x−4y=−15

once you done that you'll have to think about what variable are you trying to get be itself which in this case it'll be x. So now you'll be solving this equation.

−x+4y=−3

next you'll add -4y to both sides

Once you done so you should have this written down

-x over -1 = 4y- 3 over -1

divide -1 to both sides and you should end up with x= 4y+3

Now you have to substitute 4y+3 for x in -5x-4y=-15

So it should look like this now

−5(4y+3)−4y=−15

The next step is to simplify both sides with the following equation

−24y−15=−15

After simplifying add 15 to both sides, It then should look like this

−24y=0

Divide -24 to both sides and your answer should be this

y=0

hope this helps :)

User Connor Neville
by
5.0k points